SafeSOLO : Enhancing Women's Safety through Mobile Learning and Augmented Reality - Lee, Ling Yi; A Hamid, Rahayu (Applied Information Technology And Computer Science, 2024)
Women's safety has always been a concerning issue in our society. The use of mobile applications as a new approach in response to violence against women has grown significantly yet many focus solely on safety features rather than lasting knowledge. Empowering women with safety knowledge is crucial. Augmented Reality (AR) technology is now  widely used in several fields, including the educational industry. This project proposes the SafeSOLO mobile learning application that educates on women's safety through an immersive and engaging learning experience. Since the real-life scenarios can be dangerous, AR simulations provide visualizations and better understandings. Implementation of this project follows the Mobile Content Development (MMCD) approach. Targeting women aged 18 to 34, beta testing shows a positive result of 88.08% based on the System Usability Scale, confirming the app delivers on its claims and accepted by users.